COMMON USES OF EDIBLE PLANTS IN THE COQUIMBO REGION, CHILE - Eduardo Antonio Jaime Muñoz (Boletín Geográfico)
The present case study is related to the importance of edible plants present in the mostazal valley, Monte Patria commune, Limarí province, Coquimbo region. The objective of the work is to identify and recognize edible plants in the mostazal valley. The study area was delimited with the help of the computer program Google Earth, bibliographic material was used to identify the plants and with some villagers help, their common names were recognized; some didactic schemes were done to organize and describe the information. A list is made with the geographical points where the plants were found, differentiating their natural habitats, the origin of the species and some applications in traditional peasant food. The results of this study will allow to know these vegetables, their characteristics and the threats, creating an attitude of respect and appreciation of these natural resources.